2010
DOI: 10.2174/22102892010010100219
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Antioxidants: Next Phase of Pharmacological Effort to Fight Oxidative Stress?

Abstract: Abstract:The focus in the research of antioxidants is notably displaced in favour of research of enzyme derivatives. Extracellular superoxide dismutase (EC-SOD) is of the particular interest, as it demonstrates in vivo the protective action against development of atherosclerosis, hypertension, heart failure, diabetes mellitus. The reliable association of coronary artery disease with the decreased level of heparin-released EC-SOD was established in clinical researches. To base and develop antioxidant therapy, v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
(79 reference statements)
2
1
0
1
Order By: Relevance
“….01µ mole/L after sixth weeks, the increase in plasma GSH level in the DRD rabbits may be due to the novo GSH synthesis or GSH regeneration. The reducted glutathione, is required for activity of glutathione peroxidase and its quantity in case of oxidative stress is rather limited , that reduces the importance of this enzyme for the medical purposes [32] .The present finding strongly suggests that the use of resveratrol derivative helpful in preventing Diabetic complication in rabbits .These results are in accordance with other studies that the number of medical plant extracts possess as radical scavenging [33] . …”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“….01µ mole/L after sixth weeks, the increase in plasma GSH level in the DRD rabbits may be due to the novo GSH synthesis or GSH regeneration. The reducted glutathione, is required for activity of glutathione peroxidase and its quantity in case of oxidative stress is rather limited , that reduces the importance of this enzyme for the medical purposes [32] .The present finding strongly suggests that the use of resveratrol derivative helpful in preventing Diabetic complication in rabbits .These results are in accordance with other studies that the number of medical plant extracts possess as radical scavenging [33] . …”
Section: Resultssupporting
confidence: 91%
“…From our results we concluded that resveratrol increases the activities of antioxidant enzyme in alloxan treated rabbits implying that resveratrol reactivates the antioxidant defense system, thereby increasing antidiabetic activity [27] . Data on the effect of resveratrol derivative on Gp x activity are present in Figure(5).The increased activity of Gp x in resveratrol treated rabbits 93.96±0.07 U/L after three weeks as compared with control group100.6±0.06u/ml and 119.77±0.01U/L after sixth weeks, suggest that resveratrol has free radical scavenging activity , which may exert a beneficial effect against pathological alteration caused by reaction oxygen species .Ajith and Janaradhana (2001) mentioned in diabetes, non-enzymatic glycation due to persistent hyperglycemia may also inactivate the antioxidant enzyme , this results was in agreement with [32] . Regarding non -enzymic antioxidants, GSH is a critical determination to tissue susceptibility to oxidative damage and depletion of GSH has been shown to be associated with an enhanced toxicity to chemicals including diabetic status .…”
Section: Resultssupporting
confidence: 77%
“…SOD scavenges superoxide anion radical into hydrogen peroxide, which, in turn, is transformed to water and oxygen by catalase and GPx. These enzymes are altogether referred to as the first line of antioxidant defense enzymes against free radical-induced toxicity (Maksimenko et al, 2010; Salman et al, 2017). The slight reduction, albeit insignificant, in the plasma SOD activity of lead-exposed rats suggests that superoxide generation has little contribution to lead-induced generation of free radicals.…”
Section: Discussionmentioning
confidence: 99%
“… ïëàçìå êðîâè, íàðÿäó ñ ôåðìåíòíûìè ñèñòåìàìè, çíà-÷èòåëüíûé âêëàä â ÀÎÏ âíîñÿò ýêçîãåííûå íèçêîìîëåêóëÿðíûå àíòèîêñèäàíòû (ÀÎ), ïîñòóïàþùèå â îðãàíèçì ñ ïèùåé, ïèùåâûìè äîáàâêàìè è ëåêàðñòâåííûìè ñðåäñòâàìè [5]. Ãèïåðãëèêåìèÿ âûçûâàåò ãëèêîçèëèðîâàíèå è èíàêòèâàöèþ àíòèîêñèäàíòíûõ ôåðìåíòîâ, à ñíèaeåííàÿ àêòèâíîñòü ÑÎÄ è óìåíüøåíèå äîñòóïíîñòè ãëóòàòèîíà ÿâëÿþòñÿ èíäèêàòîðàìè íàëè÷èÿ õðîíè÷åñêîãî ÎÑ [6]. Ê íàñòîÿùåìó âðåìåíè íàêîïëåíî äîñòàòî÷íî ýêñïåðèìåíòàëüíûõ è êëèíè÷åñêèõ äàííûõ, ïîäòâåðaeäàþùèõ ýôôåêòèâíîñòü ïðèìåíåíèÿ ÀÎ â êà÷åñòâå âñïîìîãàòåëüíûõ ñðåäñòâ ïðè ëå-÷åíèè ÑÄ.…”
unclassified